Favorable Outcome of Electively Delayed Elongation Procedure in Long-Gap Esophageal Atresia - Oliver, Diez H.; Martin, Sidler; Belkis, Diez-Mendiondo I.; Lucas, Wessel M.; Steffan, Loff (Frontiers in Surgery, 2021)
The ideal approach to long gap esophageal atresia is still controversial. On one hand, preserving a patient’s native esophagus may require several steps and can be fraught with complications. On the other hand, most replacement procedures are irreversible and disrupt gastrointestinal physiology. The purpose of this study was to evaluate the short- and medium-term outcome of electively delayed esophageal elongation procedures before esophageal reconstruction in patients with long-gap esophageal atresia. Since the neonatal esophagus grows over-proportionally and can increase its wall thickness in the first few months of life, we hypothesized that postponing the elongation steps until three months of age would lead to a lower complication rate. We thus retrospectively recorded complications such as mediastinitis, anastomotic leakage, stricture formation, or gastroesophageal reflux requiring surgery, and compared it to reported outcomes. In our treatment protocol, patients born with long-gap esophageal atresia underwent gastrostomy placement and were sham fed until three months of age. We then assessed the gap between the esophageal ends and started serial elongation procedures. We only proceeded to the reconstruction of the esophagus, when its length allowed a tension-free anastomosis. From April 2013 to April 2019, we treated 13 Patients with long-gap esophageal atresia. Nine patients without prior surgical procedures underwent Foker procedures. Four patients arrived with a pre-existing cervical esophagostomy and thus underwent Kimura´s procedure, two of them with a concomitant Foker elongation of the lower pouch. Esophageal reconstruction was feasible in all patients, while none of them developed mediastinitis at any point in their treatment. We managed the only anastomotic leak conservatively. Almost half of the patients did not require any further intervention following reconstruction, while three patients required multiple (≥ 5) anastomotic dilatations. All but one patient achieved full oral nutrition. Only one child required a fundoplication to manage gastroesophageal reflux symptoms. Electively delayed esophageal elongation procedures in patients with long-gap esophageal atresia allowed preservation of the native esophagus in all patients. The approach had low peri-procedural morbidity, and patients enjoy favorable functional outcomes. Therefore, we suggest considering this method in the management of patients with long-gap esophageal atresia.